Preoperative detection of pleural adhesions using pocket-sized ultrasound. (June 2021) - Sano, Atsushi; Hiranuma, Ayako; Nagashima, Makoto
Background: Although preoperative detection of pleural adhesions is important in thoracic surgery, it is not widely performed. We report the availability of a pocket-sized ultrasound device for the preoperative detection of pleural adhesions. Methods: Between September 2019 and September 2020, pleural adhesions were assessed preoperatively using a pocket-sized ultrasound device in 62 patients who underwent thoracic surgery. Evaluations were performed using the Vscan Dual Probe on the wards or just before surgery in the operating theater. We used a linear probe to scan the chest wall where the incision was scheduled, and evaluated the sliding sign. We compared ultrasound results with intraoperative findings. Results: Of the 62 patients, the sliding sign was observed in 58 patients, 56 of whom demonstrated no pleural adhesions intraoperatively. The sensitivity was 96.6%. Four patients were negative for the sliding sign; of these, three had pleural adhesions and one did not. The specificity was 75.0%. Among all 62 patients, the diagnostic accuracy of ultrasound for pleural adhesions was 95.2%. False negatives were caused by loose adhesions. False positives were caused by the absence of vertical lines on ultrasound. Accuracy was not influenced by the timing of the test. Conclusions: A pocket-sized ultrasound device was useful for the preoperative detection of pleural adhesions in thoracic surgery.